2020
DOI: 10.1016/j.jmgm.2020.107716
|View full text |Cite
|
Sign up to set email alerts
|

Virtual screening and molecular dynamics study of approved drugs as inhibitors of spike protein S1 domain and ACE2 interaction in SARS-CoV-2

Abstract: Background The receptor binding domain (RBD) of spike protein S1 domain SARS-CoV-2 plays a key role in the interaction with ACE2, which leads to subsequent S2 domain mediated membrane fusion and incorporation of viral RNA into host cells. In this study we tend to repurpose already approved drugs as inhibitors of the interaction between S1-RBD and the ACE2 receptor. Methods 2456 approved drugs were screened against the RBD of S1 protein of SARS-CoV-2 (target PDB ID: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 37 publications
0
50
0
Order By: Relevance
“…MIGLITOL showed significant performance as an inhibitor against the spike protein (S1) of the SARS-CoV-2 virus. This result was identified using the study of molecular dynamics and virtual screening of MIGLITOL and also a number of approved drugs [ 60 ]. The effect of the coenzyme Q10 drug compound can be supportive for COVID-19 patients as it increases energy level, immunity and reduce oxidative stress among patients.…”
Section: Discussionmentioning
confidence: 99%
“…MIGLITOL showed significant performance as an inhibitor against the spike protein (S1) of the SARS-CoV-2 virus. This result was identified using the study of molecular dynamics and virtual screening of MIGLITOL and also a number of approved drugs [ 60 ]. The effect of the coenzyme Q10 drug compound can be supportive for COVID-19 patients as it increases energy level, immunity and reduce oxidative stress among patients.…”
Section: Discussionmentioning
confidence: 99%
“…In silico studies for docking and molecular dynamics simulation processes have also predicted the interaction ability of S glycoprotein RBD with various molecules related to the field of glycobiology corresponding to repurposed Food and Drug Administration (FDA)-approved drugs ( Table 1 and Figure 5 ). Several aminoglycoside antibiotics such as Kanamycin and Amikacin, and polysaccharides as Acarbose molecules showed important interaction with S glycoprotein RBD ( 83 ). RBD amino acids described to be involved in the interaction with Amikacin (R403, E406, K417, Y453, and Y495) are interspersed with those interacting with HS (R346, F347, S349, N354, R355, K444, G447, Y449, Y451 and R466), thus suggesting to be all in the same glycan-binding pocket.…”
Section: Glycobiological Human Defense To Sars-cov-2 Infectionmentioning
confidence: 99%
“…in a multimodal network-biology based study on SARS-CoV-2 human interactome, folic acid was predicted as a top candidate for drug repurposition (16 th rank) [2] as agent for re-purposing against COVID-19. In in-silico studies, folic acid is found to bind to NSP-13 [3] , furin [4] , spike:ACE2 interface [5] , [6] , PLPro [5] , MPro [5] and NSP15 [5] of SARS-CoV-2, which are important targets from drug design perspective.…”
Section: Introductionmentioning
confidence: 99%